The Formulaic Structure Analysis in Markus Zusak’s I Am the Messenger - M. Novan Maha Putra (Faculty Humanities, 2024)
I Am the Messenger is a novel written by Markus Zusak which was published in 2002. This thesis discusses the formula in I Am the Messenger using formulaic theory by John G. Cawelti (1976) to finish this thesis. The formula in this novel is done by finding the narrative structure in the novel such as plot, setting, character and characterization as the standardization aspect based on Cawelti’s theory. It helps to find out the uniqueness of this novel which make different from previous novels. After that, this thesis is continued by finding the role of social justice in Australian society through the novel as the escapism aspect based on Cawelti’s theory. This thesis using the qualitative research. There are two types of data, Primary and secondary data. The primary data are taken from Markus Zusak’s novel I Am the Messenger. The secondary data are taken from books, journals, articles, and website from internet which are related to the role of social justice in Australian society. As a result, it can be concluded that I Am the Messenger uses the popular pattern adventure and mystery as the dominant pattern. The setting here using Australia as the background of the story. Ed Kennedy as the main character has to complete missions given by “the stranger” through the playing card. He must face the struggles and obstacles when he receives the first playing card. Ed’s life completely changed after he completed all of the missions. He became the messenger for society and a reminder that if ordinary people like Ed could stand up and do what he did for all those people, well, maybe everyone could. Maybe everyone can live beyond what they’re capable of. Through the standardization of the novel, the reader is offered to escape from the reality. However, it doesn’t mean that the real life is different from the novel. Zusak uses the social problem as the main issue of this novel that must be completed by Ed as the messenger. It closely related to how the society in Australia has so many problems regarding social injustice that occur at that time. That issue has attracted the government's attention, as resolving it could make Australia more developed.
reupload file repositori 19 Februari 2026_Kholif/Keysa
Keywords: Formulaic Structure; Messenger